Cross-Cultural Measurement Invariance of Scales Assessing Stigma and Attitude to Seeking Professional Psychological Help - Zhou, Yan; Lemmer, Gunnar; Xu, Jing; Rief, Winfried (Frontiers in Psychology, 2019)
There has been a growing interest in research on stigma and attitude towards psychotherapy, and these variables are expected to show cross-cultural variations. The Stigma Scale for Receiving Psychological Help (SSRPH), the Self-Stigma of Seeking Help (SSOSH) and the Inventory of Attitudes to Seeking Mental Health Services (IASMHS) are widely used and this study examined their measurement invariance as this is a prerequisite for use in cross-cultural studies. Data were collected online from groups of Chinese students in China (n = 413) and German students in Germany (n = 416). Confirmatory factor analyses in single samples and measurement invariance testing in a multi-group framework were conducted to test the cross-group equivalence. Findings demonstrate that the SSRPH and the modified model of IASMHS had partial scalar measurement invariance, but the SSOSH showed cultural variance in factor structure. Comparisons of latent means indicated no differences between the two groups with respect to the social stigma attached to professional psychological help, but a higher psychological openness of Chinese students towards help-seeking. Findings are discussed from intercultural and methodological perspectives. In the future, intercultural cooperation should be promoted in order to develop a cross-culturally valid concept of stigma against psychological help that could be used as the basis for intercultural comparison and developing interventions to reduce stigma.